(untitled) (Iranian Journal of Kidney Diseases, 2011)
Urogenital tuberculosis (TB) is a common late manifestation of an earlier symptomatic or asymptomatic pulmonary TB infection. A latency period ranging from 5 to 40 years between the time of the initial infection and the expression of urogenital TB frequently occurs. As one of the most common sites of involvement of extrapulmonary TB, urogenital TB accounts for 15% to 20% of the infections. We present a patient who had culture-negative active tubercular kidney disease due to silent tuberculous infection. Our case demonstrates the limitations of noninvasive testing in establishing the diagnosis of renal tuberculosis.